A comparative study of some biomechanical variables of electrical activity of the muscle of the upper body between the front and back diagonal strikes in table tennis for men - Omar Fadhil Omar Al-Hamdani; Wadie Yassin Al-Tikrity (RES MILITARIS, 2022)
The benefit of electromyography of the muscles is that it can be used as a diagnostic procedure that a doctor or researcher can use to evaluate the health status of that muscle and the neurons that control it. These neurons are known as motor neurons. The electrical signals cause the muscles to contract and relax and the EMG values convert these signals into graphs or numbers which help doctors and researchers to diagnose muscle and nerve function. (Al-Tikriti. 2020. 229) The research aims to identify the values of multiple variables of electromyography activity for some of the upper body muscles between the front and back diagonal strikes in table tennis for men and the difference between them. The descriptive approach was used in comparative methods. The sample consisted of (6) advanced players. After reviewing a number of sources that used the ball throwing device, the most frequent test in the diagonal and straight research was chosen which is the front and back stroke tests (diagonal and straight) in table tennis .EMG was used to following muscles: Wrist Flexor-Biceps-Pectorals Major-Posterior part Deltoid-Trapezius-Rectus Abdominals. The researchers used arithmetic mean, standard deviation, and Wilcoxon matched-paired single range non-parametric statistical test. The following conclusions were reached There were significant differences in the variable of biceps brachii muscle in Average crowding force between the diagonal strike forehand and the diagonal strike backhand in table tennis, and for the benefit of the backhand kick. There were significant differences in the variable Maximum crowding force in forearm flexors muscle variables between the diagonal strike forehand and the diagonal strike backhand in table tennis in dorsal trapezius muscle, and for the benefit of the forehand strike. There were no significant differences were found in other variables between the diagonal strike forehand and the diagonal strike backhand in the other muscles.